(3cJGH GddGeGJs - (3CMeO Hf eMeO Hf ESeGYjd GdeUQj GdfMhj, CHh LYaQ , GHf GdfMGS, J (B338 (3g` s ((3eMehO UObi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjekG HJaSjQgG aChdgG dGe GdbSe (B( (3cdG djfHPf ai GdMWeI (B) (3EYde QMec Gddg Cf dGe GdbSe efUhHI ai PGJgG hJCJi ai BNQ GdcdGe s
(3BNQgG (B:s
(3hcPdc (B( (3djZaQ dc Gddg eG JbOe ef PfHc heG JCNQ (B) (3eYfGg dci jYaQ Gddg dc agPG dGe ci heG CTHggG GfJgi HMeO Gddg JYGdi hMSf Yhfg hJhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B208s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs